The Transformation of Islamic Politics in the Prabowo Subianto Era: The Coalition of Islamic Party Organizations and Its Implications for Indonesian Democracy - Alghifari Hafizh Matin; Clarisa Agustina; Najla Qanita Khairunnisa; Muhamad Parhan (Universitas Islam Negeri Raden Intan Lampung, 2025)
This study analyzes the role of Islamic parties in the Indonesia Onward Coalition after the 2024 elections and its impact on the quality of democracy in Indonesia. This research is a descriptive qualitative analytical-interpretive study, using primary data in the form of official documents from the four main Islamic parties: PKB, PAN, PPP, and PKS, regulations, and jurisprudence, as well as secondary data in the form of scientific articles, previous research, and media reports, with data analysis using content analysis. The results show that most Islamic parties chose a political strategy by joining the government coalition to gain policy influence, rather than to fight for ideology. PKS is the only Islamic party that consistently remains in the opposition and functions as a counterweight to democracy. The involvement of Islamic parties in the Indonesia Coalition strengthens political stability, but also implements democratic oversight mechanisms due to the reduced role of the opposition.